2017
DOI: 10.4103/ijccm.ijccm_10_17
|View full text |Cite
|
Sign up to set email alerts
|

Studying the power of the integrative weaning index in predicting the success rate of the spontaneous breathing trial in patients under mechanical ventilation

Abstract: Background and Aims:The use of weaning predictive indicators can avoid early extubation and wrongful prolonged mechanical ventilation. This study aimed to determine the power of the integrative weaning index (IWI) in predicting the success rate of the spontaneous breathing trial (SBT) in patients under mechanical ventilation.Materials and Methods:In this prospective study, 105 patients undergoing mechanical ventilation for over 48 h were enrolled. Before weaning initiation, the IWI was calculated and based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Also, similar findings were reported by [13] who examined the accuracy of IWI in predicting weaning among 50 mechanically ventilated patients for more than 72 hours and revealed that Integrative weaning index is a significant predictor of weaning and high IWI score was associated with successful weaning rate. Similar findings reported by [10] who examined the success rate of the Spontaneous breathing trial in mechanically ventilated patients and revealed that the IWI is a more www.nursingjournal.net objective indicator of SBT. However, the findings of the current study are different from [30] findings that compared the efficiency of some predictors for successful weaning from mechanical ventilation in different weaning modes and revealed that there was no significant difference regarding IWI.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Also, similar findings were reported by [13] who examined the accuracy of IWI in predicting weaning among 50 mechanically ventilated patients for more than 72 hours and revealed that Integrative weaning index is a significant predictor of weaning and high IWI score was associated with successful weaning rate. Similar findings reported by [10] who examined the success rate of the Spontaneous breathing trial in mechanically ventilated patients and revealed that the IWI is a more www.nursingjournal.net objective indicator of SBT. However, the findings of the current study are different from [30] findings that compared the efficiency of some predictors for successful weaning from mechanical ventilation in different weaning modes and revealed that there was no significant difference regarding IWI.…”
Section: Discussionsupporting
confidence: 82%
“…The use of weaning indices can minimize the risk of weaning failure and complications associated with morbidity, such as re intubation [9] . The latest indices presented for predicting weaning outcomes are the Integrative Weaning Index (IWI) and Burns Weaning Assessment Program checklist (BWAP) which are beneficial in distinguishing reversible causes of weaning failure, stand as indicator for the following attempts [10] . The IWI index was developed by [11] which evaluate respiratory mechanics, oxygenation, and respiratory pattern in an incorporated method.…”
Section: Introductionmentioning
confidence: 99%
“…The robustness of this index has been established due to its ability to evaluate the respiratory mechanics, oxygenation, and respiratory pattern in a single equation. It has been proven to be reliable in subsequent studies by El-Baradey et al 19 and Ebrahimabadi et al 20 Multiplying the compliance by the saturation in the numerator detect the ability to maintain oxygenation, with good or bad respiratory mechanics. Dividing this by the f/VTratio (RSBI) in the denominator detects those who will or will not be able to maintain unassisted breathing.…”
Section: Discussionmentioning
confidence: 99%
“…Já em um estudo realizado em uma UTI em um hospital no Irã, com o objetivo de determinar a fidedignidade do índice de desmame para prever a taxa de sucesso/insucesso do TRE, dentro da sua análise, foi evidenciado que a FR inadequada teve correlação com os pacientes que tiveram insucesso 29 . Estes fatos podem ser explicados através da influência da disfunção cardíaca após o estresse fisiológico ocorrido durante a extubação, com o aumento da pressão intratorácica e a hiperestimulação simpática que favorece para o aumento do trabalho cardíaco e do retorno venoso ocasionando aumento do enchimento ventricular podendo expandir e precipitar o edema pulmonar 30,31,32,33,34,35 .…”
Section: Discussionunclassified